Viral hemorrhagic fevers in the Tihamah region of the western Arabian Peninsula. - Fathiah Zakham; Mohammed Al-Habal; Rola Taher; Altaf Alaoui; Mohammed El Mzibri (Public Library of Science (PLoS), 2017)
Viral hemorrhagic fever (VHF) refers to a group of diseases characterized by an acute febrile syndrome with hemorrhagic manifestations and high mortality rates caused by several families of viruses that affect humans and animals. These diseases are typically endemic in certain geographical regions and sometimes cause major outbreaks. The history of hemorrhagic fever in the Arabian Peninsula refers to the 19th century and most outbreaks were reported in the Tihamah region-the Red Sea coastal plain of the Arabian Peninsula in the west and southwest of Saudi Arabia and Yemen. Herein, we describe the agents that cause VHFs and their epidemiology in Tihamah, the history of the diseases, transmission, species affected, and clinical signs. Finally, we address challenges in the diagnosis and control of VHFs in this region.